2022
DOI: 10.1088/1361-6528/ac57d5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the mechanical and thermal transport properties of carbon nanotube yarns by boundary structure modulation

Abstract: Carbon nanotubes (CNTs) exhibit extremely high nanoscopic thermal/electrical transport and mechanical properties. However, the macroscopic properties of assembled CNTs are significantly lower than those of CNTs because of the boundary structure between the CNTs. Therefore, it is crucial to understand the relationship between the nanoscopic boundary structure in CNTs and the macroscopic properties of the assembled CNTs. Previous studies have shown that the nanoscopic phonon transport and macroscopic thermal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Brittle fracture was also found, which is in agreement with theoretical predictions and experiments in other works. [63][64][65] Besides, the SWCNT with a higher torsion degree possessed higher stretchability. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Brittle fracture was also found, which is in agreement with theoretical predictions and experiments in other works. [63][64][65] Besides, the SWCNT with a higher torsion degree possessed higher stretchability. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes the latter dominates the physical properties such as the thermal, electrical, and mechanical properties. [1][2][3][4][5][6][7][8][9] The junctions have poor thermal conductance, electrical conductance, and mechanical strength due to the vdW interactions, which are drastically weaker than the in-plane covalent bondings of CNTs. [10][11][12][13][14][15][16] Furthermore, it has been suggested that the transport properties of nanotubes themselves could be affected by the intertube interactions.…”
mentioning
confidence: 99%